"Cultural awareness requires more than theoretical education" - Nursing students' experiences. (August 2019) - Hultsjö, Sally; Bachrach-Lindström, Margareta; Safipour, Jalal; Hadziabdic, Emina
Abstract: Cultural awareness in healthcare providers is considered one of the most important factors in improving the efficiency and quality of care in a diverse population. Thus, education in cultural awareness needs to be an essential component in nursing education. This study, which uses a qualitative design, aimed to investigate cultural awareness in nursing students in Sweden. Focus groups were used to collect data from 12 students. Three categories were identified as follows after qualitative data analysis of the interviews: 1) desire to learn, 2) learning by doing and 3) caring beyond boundaries. The result clearly indicates that students are willing to learn more about how to care for people with different cultural backgrounds. However, this learning is not always available in official lecture-based education. In fact, most awareness about cultural aspects of healthcare is developed from practice and informal education. Finally, the result also revealed the importance of nurses being able to see the individual beyond the culture, and being aware of their own prejudice. In conclusion, education offers limited opportunities for nursing students to become culturally aware. Nursing education can be improved by strengthening both theoretical and practical tasks involving cultural awareness. Highlights: To support students in their cultural awareness, nursing education should involve cultural values, behaviours and norms. Incorporating practical, culture-related training can benefit students in terms of improving their cultural awareness. Nursing students need to be challenged and discuss their own values and prejudices in order to develop self-awareness.